Peningkatan Kreativitas dan Pemahaman Lingkungan melalui Workshop Eco Print di Desa Padang Cermin: Upaya Penguatan Pendidikan Berbasis Kearifan Lokal - Najah, Zughrofiyatun; Regina Utami, Salsa (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
The Eco Print Workshop in Desa Padang Cermin was designed with the primary goal of enhancing creativity and environmental awareness among members of the Risma group and local school children. Through this hands-on training, participants were introduced to the process of utilizing natural materials, such as leaves and local plants, to create unique patterns on fabric using eco-printing techniques. This method not only emphasized the artistic aspect but also the importance of sustainability by harnessing resources that are readily available in the surrounding environment. The evaluation of the workshop's effectiveness revealed significant improvements across several key areas: conceptual understanding, practical skills, creativity, and environmental consciousness. Participants demonstrated a marked increase in their ability to understand and apply the principles of eco-printing, creatively develop their own designs, and recognize the broader environmental implications of their work. This workshop successfully provided participants with new, practical skills while fostering a deeper appreciation for sustainable practices and the natural world. However, the program did face some challenges, primarily related to time constraints and the limited availability of materials, which were mitigated through a well-structured approach to the workshop’s delivery. To maximize the impact of similar future initiatives, it is recommended that the duration of the training be extended and that efforts be made to include a more diverse group of participants. Such improvements would likely broaden the reach and effectiveness of the program, thereby contributing to a more widespread adoption of eco-friendly practices in the community.